INVESTASI DALAM PERSEPEKTIF ISLAM - Yuliana, Indah (IQTISHODUNA, 2010)
Investment is a part of important thing in investment economic that is activity including risk because it faces with uncertainty element. Islam as comprehensive religion in its studying and norm manage the whole human activity in all field. Islam motivates every person for working and reaching wealth as much as possible. It allows every human to look for a wealth as much as he or she can, increase, use during it does not disturb norm of religion. Islamic economic investment is different from economic investment non Moslem. It is primarily caused in Islamic economic investment without using interest level in calculating investment. Asset or money is assessed by Allah as a fundamental tool in this life. Therefore, asset and financial capital are not allowed to gain for their selves but it should be by human effort. That is one of causes why using money in excessive interest forbidden by Al-Qur’an. Investment in Islam is muamalah activity that is very suggested because it makes asset to be productive and gives advantage for others. Investment in perspective of economic Islam is not only about profit which is gained from investment activity, but there are several motivations of investment in Islam.